Synthesis and in vitro activity of new methylenepiperidinyl and methylenepyrrolidinyl oxazolidinone antibacterial agents - Kim, HY; Lee, JS; Cha, JH; Pae, AN; Cho, YS; Chang, MH; Koh, HY (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
We have prepared and evaluated the antibacterial activities of a series of substituted methylenepiperidinyl and methyl-enepyrrolidinyl oxazolidinones against several gram-positive strains including the resistant strains of Staphyloccus and Enterococcus, such as MRSA, CRSA, MSSA and VRE. Some of them showed comparable or superior in vitro activities (MIC) to vancomycin. (C) 2003 Elsevier Science Ltd. All rights reserved.